Identification of Three Autophagy-Related Long Non-Coding RNAs as a Novel Head and Neck Squamous Cell Carcinoma Prognostic Signature - Guo, Ya; Yang, Peng Tao; Wang, Zhong Wei; Xu, Kun; Kou, Wei Hua; Luo, Heng (Frontiers in Oncology, 2021)
Head and neck squamous cell carcinoma (HNSCC) has a poor prognosis. Considerable evidence indicates that autophagy and non-coding RNA play essential roles in the biological processes involved in cancers, but associations between autophagy-related long non-coding RNAs (lncRNAs) and HNSCC remain unclear. In the current study HNSCC RNA sequences and autophagy-related gene data were extracted from the Cancer Genome Atlas database and the Human Autophagy Database. A total of 1153 autophagy-related lncRNAs were selected via co-expression analysis. Three autophagy-related prognostic lncRNAs were identified via univariate analysis, least absolute shrinkage and selection operator analysis, and multivariate Cox regression analysis. Time-dependent receiver operating characteristic and Kaplan-Meier survival analysis were performed to evaluate the prognostic accuracy of the model. The area under the curve (AUC) was 0.864 (3-year) and 0.836 (5-year). Patients with a low-risk scores had a better survival rate. The prognostic value of the three lncRNAs identified was confirmed via analysis of samples from five databases. To further identify the functions of the three lncRNAs, a co-expression network was constructed and pathway analysis was performed. In that analysis the lncRNAs were correlated with 189 related genes and 20 autophagy-related genes, and these IncRNAs mainly involved homologous recombination, the Fanconi anemia pathway, the autophagy-related pathway, and immune-related pathways. In addition, we validated the expression levels of three IncRNAs and autophagy markers (ATG12, BECN1 and MAP1LC3B) based on TIMER, Oncomine and HPA database analysis. Our results indicated that TTTY15 was increased in HPV positive and HPV negative HNSCC patients, and three autophagy markers were up-regulated in all HNSCCC patients. Lastly, association between three IncRNAs and autophagy markers was performed, our results showed that TTTY15 and MIF-AS1 were associated with autophagy markers. Collectively these results suggest that three autophagy-related lncRNAs identified have prognostic value in HNSCC patients.